Strategic management model of the learning environment in the era of digital transformation: Empirical studies in Indonesian educational institutions - Indarti, Nunuk; Pamungkas, Onok Yayang; Mastiyah, Iyoh; Wardani, Yani’ah; Herlinawati; Hanun, Farida; Ma’rifataini, Lisa’diyah; Dudin, Achmad; Habibullah, Achmad; Astuti, Marhanani Tri; Suherman (Research Journal in Advanced Humanities, 2026)
This article examines the strategic management model of the language learning environment in the era of digital transformation with a focus on the role of educators and institutional governance in Indonesia. The study used cross-sectional quantitative design at 240 institutions in 31 provinces, including junior high schools, high schools/vocational schools, and colleges. Key variables include institutional strategy maturity, educator digital competencies, AI utilization, and LMS adoption. The outcome is an increase in standardized language proficiency at the institutional level. The descriptive results showed an average strategy maturity of 1.99/5, digital competence of 64.57/100, an infrastructure index of 0.664/1, and LMS adoption of 16.7%. The leaning OLS model explains ≈62% variation in outcomes. The largest contribution comes from digital competence and the use of AI, followed by the direct effect of strategy maturity. The mediation analysis showed that part of the influence of the strategy flowed through digital competencies and AI practices, while the moderation test showed that the strategy effect was stronger in urban institutions than in semi-urban and rural. Robustness checks (HC3-robust SE, specification curve, winsorizing/trimming, and leave-one-province-out) confirm the coefficient stability and smallness of ΔR² between specifications. The findings confirm that a clear strategy architecture, educators' digital competence, and an adequate analytics ecosystem are prerequisites for reaping the academic impact of language learning technologies. The practical implications emphasize policy priorities on strengthening teachers' digital competencies, curriculum-based AI/LMS orchestration, as well as improving the conditions of data facilitation and governance, especially to bridge the gap between regions.